Facts to the landscape history of the Öreg-Bakony Mountains - Saláta, Dénes; Penksza, Károly; Malatinszky, Ákos; Kenéz, Árpád (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
In the past, Hungarian land use and the landscape itself, was much more colourful and diverse than it is today. Processes and effects resulting in the current state of landscapes are explored during landscape history studies of certain areas. These changes are being examined in the once vast, dense forests covering the Carpathian Basin. These forests have been significantly reduced due to habitat alteration, and their view has changed due to shifting land use. One of the largest forested areas in Hungary is the Bakony Mountains, but its coverage has also decreased significantly during the past 500–1000 years in tandem with traditional agriculture and forestry, which are slowly disappearing as production becomes intensive. Traditions of the Öreg-Bakony (the central and highest part of the Bakony Mountains) accurately portray quondam and irreplaceable customs of the Bakony Mountains. These customs included hogs foraging for acorns, other livestock grazing in the forests, use of tree foliage as fodder or collecting dead fallen leaves, and were everyday practices even in the 19th century. Some geographical names of the area refer to wood-based industries, strengthening their importance in the area.